ANALISIS VEGETASI JENIS POHON DI KAWASAN HUTAN KAMPUNG WASUR PADA TAMAN NASIONAL WASUR DISTRIK MERAUKE KABUPATEN MERAUKE - Yosefina Mangera (AGRICOLA, 2011)
This study is aimed to find out the composition, structure, and the ecological value of the types of trees in the exploitation zone of the National Wasur Park. The method used was square method, documentation, and literary study. Type variety index of Shannon-Wiener was employed to determine the variety types of the trees. The result of the research and data analysis showed that at the big tree category there were 16 types, 8 families, and 76 individuals. Meanwhile, at the small tree category, there were 12 types, 8 families, and 71 individuals. Analyzing the height structure, it was found out that Lophostemon lactifluus (F. Muell) Peter G. Wilson & J.T. Waterh (INP 54.74%) was the highest INP at the big tree category. Meanwhile, at the small tree category, the highest INP was Planchonia careya (F. Muell) R. Knuth (INP 68.82%). Therefore, the vegetation in the exploitation zone was considered as the Lophostemon lactifluus (F. Muell) Peter G. Wilson & J.T. Waterh and Planchonia careya (F. Muell) R. Knuth. The type variety index (H’) at the big tree and the small tree category were 2.43 and 2.9 respectively. These indexes were considered low. The ecological values of the forest were as the water diffusion area, system prop of life, and habitat of some animals such as various insect types, mammals and birds.